Respuesta :
Answer:
x = 6 2/3
Step-by-step explanation:
10+3(x+2)=36
10+3x+6=36 Solve inside the parenthesis.
16+3x=36 Combine like terms.
-16 -16 Subtract 16 from both sides.
3x/3=20/3 Divide both sides by 3.
x=6 2/3 The answer is x= 6 2/3, or 6.66666666666667
Answer:
x = 6 2/3
Step-by-step explanation:
10 + 3 (x + 2) = 36
Distribute 3 into (x + 2)
10 + 3 x X + 3 x 2 = 36
10 + 3x + 6 = 36
The expression can also be written as
10 + 6 + 3x = 36
16 + 3x = 36
Subtract 16 from both sides
16 - 16 + 3x = 36 - 16
3x = 20
Divide both sides by 3
3x/3 = 20/3
x = 6 2/3